Antibacterial Activity of Ag-Hidroxyapatite Composite of Bone-in Tuna (Thunnus albacores) Against Streptococcus mutans - Hendri Faisal; Rida Evalina Tarigan; Julkardo Lase (JURNAL SAINS NATURAL, 2022)
Calcium from fish bones have not been widely used for human needs. Calcium in the medical field is used as a hydroxyapatite compound, such as in the manufacture of bones and dentures, as an additive in the manufacture of toothpaste, and usage in drug delivery. This study aims to determine whether the Ag-Hydroxyapatite composite has an inhibitory capability against Streptococcus mutans bacteria. This research is an experimental study through laboratory testing by synthesizing Ag-Hydroxyapatite from tuna fish bones (Thunnus albacores) and testing its antibacterial activity against Streptococcus mutans bacteria. The results showed that the tuna fish bone samples formed hydroxyapatite compounds and the results of the Ag-Hydroxyapatite composite had antibacterial activity against Streptococcus mutans bacteria, the statistical test results showed a significant difference from the negative control group. Ag-hydroxyapatite composite has antibacterial activity against Streptococcus mutansKeywords: Tuna (Thunnus albacores); Hydroxyapatite; Argentum; Antibacterial; Streptococcus mutans ABSTRAKUji Aktivitas Antibakteri Komposit Ag-Hidroksidaapatit dari Tulang Ikan Tuna (Thunnus albacores) terhadap Streptococcus mutansKalsium dari tulang ikan, belum banyak dimanfaatkan untuk kebutuhan manusia. Kalsium dalam dunia medis dimanfaatkan menjadi senyawa Hidroksiapatit. seperti pada pembuatan tulang dan gigi palsu, sebagai bahan tambahan dalam pembuatan pasta gigi dan juga digunakan sebagai penghantar obat. Penelitian ini bertujuan untuk mengetahui apakah komposit Ag-Hidroksiapatit memiliki daya hambat terhadap bakteri Streptococcus mutans. Penelitian ini merupakan penelitian yang bersifat eksperimental melalui pengujian laboratorium dengan mensintesis Ag-Hidroksiapatit dari tulang ikan tuna (Thunnus albacores) dan menguji aktivitas antibakteri terhadap bakteri Streptococcus mutans. Hasil penelitian menunjukan bahwa dari sampel tulang ikan tuna terbentuk senyawa Hidroksiapatit dan hasil komposit Ag-Hidroksiapatit memiliki aktifitas antibakteri terhadap bakteri Streptococcus mutans, hasil uji statistik menunjukkan adanya perbedaan signifikan terhadap kelompok kontrol negatif.  Komposit Ag-hidrokiapatit memiliki aktifitas antibakteri terhadap bakteri Streptococcus mutansKeywords: Tuna (Thunnus albacores); Hydroxyapatite; Argentum; Antibacterial; Streptococcus mutans